Dual-band aperture coupled antenna with harmonic suppression capability - Faza Syahirah Mohd Noor; Zahriladha Zakaria; Herwansyah Lago; Maizatul Alice Meor Said (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
The paper presents an aperture-coupled dual-band linearly-polarized antenna with harmonic suppression capability, operating at frequency 2.45 GHz and 5.00 GHz. In purpose of improving the directivity of antenna at the operating frequency of 2.45 GHz and 5.00 GHz, a modified inverted π-shaped slot-etched patch on the lower layer of the stacked antenna is introduced alongside the 50 Ω feed line. The harmonic suppression capability is achieved by the introduction of U-slot and asymmetrical left-right-handed stub at the transmission feed line, suppressing unwanted harmonic signals from 6.00 GHz up to 10.00 GHz. The final design of the antenna has produced very good reflection coefficient of -18.87 dB at 2.45 GHz and -19.57 dB at 5.00 GHz with third and higher order harmonic suppression up to -4 dB.